Enhanced performance of PID load frequency controller for power systems - Dola Gobinda Padhan; Suresh Kumar Tummala (International Journal of Advances in Applied Sciences, 2019)
A novel control structure for designing a PID load frequency controller for power systems is presented. The controller with a single tuning parameter is designed based on a desired closed-loop complementary sensitivity function and Pade approximation. Comparative analysis demonstrates that proposed PID controllers improves the settling time and reduces overshoot effectively against small step load disturbances. Also, the performance and robustness of the controllers have been analyzed and compared. Simulation results show significantly improved performances when compared with recent results.